Psikologi Agama dalam Perkembangan Psikologi pada Umumnya. - Sekar Ayu Aryani (Al-Jami'ah Research Centre, 1997)
Psychology and Religion are two essential components in Religions Psychology. In Its long history, The psychology has been dominated by pulling each other between supporters of both components, psycholog and religious scholars, to bring an emphasis on their own discipline. The paper tries to analyses the possibility of putting religious mission on it, for the discipline is said to be more psychological than religious. The analysis is based on its historical development history as well as the hopes of the era, especially the hopes from the religion as a social institution. The chance of the rise of Religious Psychology in Religion psychology will be drawn in a position in which the school of status quo faces the school of counter culture. Here, the school of counter culture is not seen as a threat for mainstream anymore; it may evev fertilize and enriche the major school.